Existence of Unique and Global Asymptotically Stable Almost Periodic Solution of a Discrete Predator-Prey System with Beddington-DeAngelis Functional Response and Density Dependent (2018)
The main concern of this paper is to study the dynamics of a discrete predator-prey system with Beddington-DeAngelis functional response and density dependent predator, assuming that the coecients involved in the system are almost periodic. More concretely, under certain conditions, we prove the existence of a unique almost periodic solution which is globally attractive. We exhibit a few numerical examples of the results.